COMMUNITY ANALYSIS OF AMPHIBIAN FAUNA IN BOLANGIR, ODISHA, INDIA - A. K. MISHRA; BHIKARI CHARAN GURU (The Bioscan, 2013)
Community analysis of amphibian fauna in Bolangir has been studied by dominance, diversity and evenness Indices. The distribution of 13 species of amphibian, collected from study sites in various habitat has been studied In paddy field, both irrigated and unirrigated, human habitation sites, both urban and rural areas, forest areas and water bodies is studied. The maximum average density of amphibian per unit area per month is 74 in water bodies, where as it is minimum of 31.8 in rural habitation sites .The Simpson dominance index is 0.2399 in water bodies and 0.1337 in urban habitation sites. The Shannon diversity index is -2.1496 in urban habitation sites and -1.7049 in water bodies. The evenness index is 0.6213, higher in urban habitation, is an indication of less variation in amphibian community, but the value is 0.5378 in water bodies indicating more variation in community. The all amphibian species sampled from the study site belongs to order Anura, where 59 % species are Ranidae, 21% Microhylidae, 14% Bufonidae and 4% Rhacophoradae. L. limnocharis species contributes 34.1% and R. variegate species contributes 0.49% of the total amphibian population. The study is focused on Bolangir owing to its significant increase of temperature in the context of global climate change.